Relationship Between Innovativeness And Performance: A Study Of Tourism Entrepreneurs In Langkawi - Bukhari, Azmil Munif Mohd (2022)
Tourism is is the largest component within the service sector which in turn the largest contributor to Malaysia’s gross domestic product (GDP). Tourism industry is in a downward spiral due to various reasons such as global economic crisis strong competition from other countries. Innovative efforts are necessary to further promote this industry to reap the full benefits and potential. Innovativeness remains one of the important factors in enhancing tourism enterprises. In view of the above, the purpose of this study is to examine the interrelationship of three innovativeness variables and performance. In addition to that, the moderating role of political networking and institutional support will also be studied. Based on responses from 126 tourism related entrepreneurs, this study conducted partial-least-square structural equation modeling analysis to test all the hyphotheses. Additionally, this study also conducted semi structured qualitative interviews to understand in detail the challenges faced by entrepreneurs. In general, market innovativeness, strategic innovativeness, political networking and institutional support positively influence performance. Furthermore, political networking moderates the relationship between all there innovativeness constructs (market, behavior and strategic) and performance. However, institutional support only moderates the relationship between market innovativeness and performance.